Novel Strategies for the Generation of Neuronal Diversity: Lessons From the Fly Visual System - Contreras, Esteban G.; Sierralta, Jimena; Oliva, Carlos (Frontiers in Molecular Neuroscience, 2019)
Among all organs of an adult animal, the central nervous system stands out because of its vast complexity and morphological diversity. During early development, the entire central nervous system develops from an apparently homogenous group of progenitors that differentiate into all neural cell types. Therefore, understanding the molecular and genetic mechanisms that give rise to the cellular and anatomical diversity of the brain is a key goal of the developmental neurobiology field. With this aim in mind, the development of the central nervous system of model organisms has been extensively studied. From more than a century, the mechanisms of neurogenesis have been studied in the fruit fly Drosophila melanogaster. The visual system comprises one of the major structures of the Drosophila brain. The visual information is collected by the eye-retina photoreceptors and then processed by the four optic lobe ganglia: the lamina, medulla, lobula and lobula plate. The molecular mechanisms that originate neuronal diversity in the optic lobe have been unveiled in the past decade. In this article, we describe the early development and differentiation of the lobula plate ganglion, from the formation of the optic placode and the inner proliferation centre to the specification of motion detection neurons. We focused specifically on how the precise combination of signalling pathways and cell-specific transcription factors patterns the pool of neural stem cells that generates the different neurons of the motion detection system.